2013
DOI: 10.1111/ede.12053
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of Bab paralog expression and abdominal pigmentation among Sophophora fruit fly species

Abstract: The evolution of gene networks lies at the heart of understanding trait divergence. Intrinsic to development is the dimension of time: a network must be altered during the correct phase of development to generate the appropriate phenotype. One model of developmental network evolution is the origination of dimorphic (male-specific) abdomen pigmentation in the fruit fly subgenus Sophophora. In Drosophila (D.) melanogaster, dimorphic pigmentation is controlled by the dimorphic expression of the paralogous Bab1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…In contrast to the conserved protein functionality that we observed for the Bab paralogs, some divergent patterns of expression have been found for the paralogs in D. melanogaster, consistent with a role for neo- or sub-functionalization (Couderc et al, 2002). Yet, the majority of bab paralog expression patterns appear to be common to both paralogs (Couderc et al, 2002; Rogers et al, 2013; Salomone et al, 2013), including the pupal abdominal epidermis, for which expression is governed by two shared CREs (Williams et al, 2008). It has been found that heterozygous bab null females have a more male-like pattern of tergite pigmentation compared to wild type females, and the homozygous null pigmentation phenotype is more or less equivalent to that of males.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the conserved protein functionality that we observed for the Bab paralogs, some divergent patterns of expression have been found for the paralogs in D. melanogaster, consistent with a role for neo- or sub-functionalization (Couderc et al, 2002). Yet, the majority of bab paralog expression patterns appear to be common to both paralogs (Couderc et al, 2002; Rogers et al, 2013; Salomone et al, 2013), including the pupal abdominal epidermis, for which expression is governed by two shared CREs (Williams et al, 2008). It has been found that heterozygous bab null females have a more male-like pattern of tergite pigmentation compared to wild type females, and the homozygous null pigmentation phenotype is more or less equivalent to that of males.…”
Section: Discussionmentioning
confidence: 99%
“…In the DGRP collection, European populations, and an African population of D. melanogaster , only SNPs in the first intron of bab1 were associated with abdominal pigmentation variation (Bastide et al 2013; Dembeck et al 2015a,b; Endler et al 2016). A cis -regulatory element controlling sex-specific expression of bab1 in the A5-A7 segments in D. melanogaster males (repression) and females (induction) was also identified in the first intron of bab1 (Williams et al 2008) and overexpression of bab1 during late pupal development was shown to be sufficient to suppress dark pigmentation (Salomone et al 2013), suggesting that the associated sites might alter pigmentation by altering expression of bab1 . Indeed, Rogers et al (2013a) found that different alleles of this element were present in lightly and darkly pigmented D. melanogaster that drove different patterns of gene expression that correlate with pigmentation in the manner expected given bab ’s role as a repressor of dark pigmentation.…”
Section: Abdominal Pigmentationmentioning
confidence: 99%
“…Changes in yellow expression often accompany changes in pigmentation between Drosophila species, but they have yet to be implicated in intraspecific variation. This might be because overexpression of yellow has more subtle effects on pigmentation than overexpression of ebony , tan , or bab1 (Wittkopp et al 2002a; Jeong et al 2008; Wittkopp et al 2009; Salomone et al 2013), such that changes in yellow expression arising alone within a species are insufficient for altering pigmentation in most populations (but see Wittkopp et al 2002b). Genetic changes in the same cis -regulatory regions have been observed within and between species, but the scope of these changes differs.…”
Section: Lessons Learned From Drosophila Pigmentationmentioning
confidence: 99%
“…The 5.3 kb intergenic sequence located 5' of the D. pseudoobscura yellow gene drove expression throughout the developing head, thorax, and abdomen ( Figure 4A, Kalay and Wittkopp 2010). Although pigmentation of this species is generally considered to be sexually monomorphic (Kopp et al 2000;Jeong et al 2006;Salomone et al 2013;Camino et al 2015), expression was elevated in the A5 and A6 abdominal segments relative to A2-A4 in males and decreased in A6 relative to A2-A5 in females. Among the sub-fragments from the 5' intergenic sequence tested ( Figure 4A), pse_B1, pse_B3, and pse_B5 all drove broad expression in the body similar to the full 5' intergenic region; however, of these three fragments, only pse_B1 drove sexually dimorphic expression similar to the full 5' intergenic sequence.…”
Section: Pupal Enhancer Activities Of D Pseudoobscura Yellowmentioning
confidence: 99%